Do autocratic states trade less? - Toke S. Aidt; Martin Gassebner (ETH Zurich, KOF Swiss Economic Institute, 2007)
The paper analyzes whether the political regime of a country influences its involvement in international trade. Firstly, we develop a theoretical model that predicts that autocracies trade less than democracies. Secondly, we test the predictions of the model empirically using a panel of more than 130 countries for the years 1962 to 2000. In contrast to the existing literature, we use data on individual importing and exporting countries, rather than a dyadic set-up. In line with the model, we find that autocracies import substantially less than democracies, even after controlling for official trade policies. This finding is very stable and does not depend on a particular set-up or estimation technique.
Keywords: F13; F14; O24; P45; P51; 330; international trade; democracy; autocracy; gravity model; Internationale Wirtschaftsbeziehungen; Außenhandelseffekt; Außenwirtschaftspolitik; Vergleich; Demokratie; Autoritäres System; Gravitationsmodell; Welt